Does political regime influence bilateral trade in West Africa?. Issue 3 (2nd July 2020) - Azu, Nnanna P.; Muhammad, Maimuna Y.
Abstract: Most regional trade agreements ascribe great importance to member country's political regimes of which preference is given to democratisation. In this paper, we investigate the influence of political regimes on bilateral trade in West Africa. We exploit two different ratings for political regime: Freedom House and Polity IV and applied Poisson pseudo maximum likelihood estimation technique. The empirical results reveal that political regime is significant to trade determination. Result portrays that generally; democratic regime positively and significantly influences bilateral trade and is homogenous in export and import. In West Africa, being import dependent, such influence is only robust as importer. We further noted that the influence of political regime on bilateral trade depends on the region and level of income; favourable to high-income Western countries. The results further indicate that two countries of similar political regimes trade less which is consistent in West African region.